Analisis Hubungan Good Corporate Governance dengan Efektifitas Corporate Social Responsibity (CSR) Pada Bank Syariah Indonesia - Septian, Ilham; Ania Kurnia; Taufiq Ramadhan; Vicy Andriany (Jurnal Manajemen Kreatif dan Inovasi, 2026)
This study aims to analyze the effectiveness of Corporate Social Responsibility (CSR) implementation at PT Bank Syariah Indonesia (BSI) and examine its relationship with the application of Good Corporate Governance (GCG). The research employs a qualitative method using a literature review approach by analyzing relevant scientific sources on CSR and GCG. The findings indicate that CSR implementation at BSI still faces challenges in program effectiveness, targeting accuracy, and alignment with community needs. The allocation of CSR funds, which tends to prioritize sports activities, national events, and ceremonial programs, suggests that the impact on economically vulnerable communities remains indirect and less optimal. This condition reflects the tendency toward symbolic CSR practices, where initiatives are oriented more toward corporate image and legitimacy than toward generating sustainable social impact. Furthermore, the study reveals that the quality of GCG implementation significantly influences CSR effectiveness, particularly regarding transparency, accountability, responsibility, and stakeholder involvement in planning and implementation. Therefore, strengthening GCG principles is essential to improve CSR planning, execution, and evaluation so that programs become more targeted, measurable, and sustainable, while contributing to theoretical understanding of CSR and GCG linkage and offering practical recommendations for companies to enhance accountability and social value creation effectively sustainably.